A Systematic Review Comparing Animal and Human Scarring Models - Mistry, Riyam; Veres, Mark; Issa, Fadi (Frontiers in Surgery, 2022)
Introduction Establishing an easily reproducible, standardised model for creating cutaneous scar tissue for assessment of treatments in both animals and humans has long been difficult to achieve. A systematic review was performed to critically evaluate scarring models in both animal and human research. Method All studies that utilized a specific model for assessing scar tissue that was purposefully created in animals or humans were included. Models that were analysing the wound healing process and those in humans with scars from an existing injury were excluded. The database Ovid Medline was searched on 25th February 2019 to perform two near identical searches; one aimed at animals and the other aimed at humans. The titles and abstracts were independently screened by the two reviewers to identify any potentially suitable studies. Full texts of potentially suitable studies were obtained and analysed. Results The animal kingdom search yielded 818 results, of which 71 were included in the review. Animals utilised included rabbits, mice, pigs, dogs and primates. Methods used include sharp excision, dermatome injury, burn and injection of fibrotic substances. The human models search yielded 287 results, of which 9 were included. All methods in human studies involved sharp incision with some focused on patients before or after elective surgery such as bilateral breast reduction, knee replacement or midline sternotomy. Discussion In the animal kingdom the rabbit ear scar model is the most popular. Immunocompetent murine models allow for in vivo culture of human scar tissue and pigs produce scar tissue most similar to humans. Factors that determine the use of animals include cost of housing requirements, genetic traceability of the animals and ethical concerns. In humans, surgical patients are popular but reproducibility and patient factors effecting healing limit current models. Human tissue use in vitro may serve as a good basis to assess treatments prior to use in live humans and have the advantage of reduced cost and set up requirements.